A highly efficient A-site deficient perovskite interlaced within two dimensional MXene nanosheets as an active electrocatalyst for hydrogen production. (30th October 2022) - Khan, Ramsha; Mehran, Muhammad Taqi; Naqvi, Salman Raza; Khoja, Asif Hussain; Baig, Mutawara Mahmood; Akram, Muhammad Aftab; Shahzad, Faisal; Hussain, Sajjad
Abstract: We report a unique composite of La0.4 Sr0.4 Ti0.9 Ni0.1 O3-δ (LSTN) nanoparticles interlaced with two dimensional Ti3 C2 Tx (MXene) nanosheets, providing high conductivity. LSTN heterostructure synthesized by the sol-gel method produces a large oxygen vacancy and creates a variable valence state while, MXene synthesized from Hydrofluoric acid (HF) treatment resulted in a highly hydrophilic and conductive surface, thereby enhancing the charge transferability. For OER, the LSTN/MXene 66.67% electrode exhibits a benchmark of 10 mA cm −2 at a potential of 1.56 (V vs RHE) in 1 M KOH. It has exhibited the lowest Tafel slope of 44 mV dec −1 and highest mass activity (60 mA g −1 @ 1.59 V) due to quicker ions diffusion and increased available exposed area. Moreover, the efficient LSTN/MXene 66.67% electrode showed good long-term durability during a 24 h stability test at a current density of 100 mA cm −2 . The strong interfacial interaction and high charge transfer among LSTN nanoparticles and 2D MXene nanosheets not only provide good structural strength to the composite but also improves the redox activity of LSTN/MXene 66.67% catalyst towards OER. This work provides improved conductive properties of perovskite by developing a composite of perovskite and MXene, that has significantly enhanced electrochemical properties of the catalyst by undergoing fast kinetics. Graphical abstract: Image 1 Highlights: La0.4 Sr0.4 Ti0.9 Ni0.1 O3-δ nanoparticles interlaced within Ti3 C2 Tx nanosheets. For OER, the LSTN/MXene 66.67% electrode exhibits 10 mA cm −2 at 1.56 V (E vs RHE). The LSTN/MXene 66.67% showed good long-term stability during a 24 h test.